PREVALENCE OF OXYTETRACYCLINE RESIDUE AND RESISTANT ESCHERICHIA COLI O157:H7 IN BEEF AND CHICKEN IN SELECTED CITIES OF SOUTH WESTERN NIGERIA (2011)
The use of antibiotics in livestock production is of food safety concern due to hazards of their residues and transfer of resistant bacteria along the food chain. There are few reported quantitative assessment of meat-borne antibiotic residues and resistant pathogens in southwestern Nigeria. Antibiotics usage in food animal production, antimicrobial residues screening, prevalence of Escherichia coli O157:H7 and levels of oxytetracycline residue in chicken and beef from Lagos, Ibadan and Akure were investigated. A semi-structured questionnaire was administered to 30 poultry and 20 cattle producers purposively selected from the study areas to obtain data on types and sources of antibiotics used, knowledge of disease recognition and practice of withdrawal periods in food animals. Two hundred and fifty samples each of kidney, liver and muscles of slaughtered cattle from one abattoir and 200 samples each of breast muscle and liver from chicken markets and broiler farms in each study area were collected between January 2006 and December 2009. The samples were screened for antimicrobial residues using rapid microbial inhibition assay. Oxytetracycline residue levels were determined by high performance liquid chromatography. Escherichia coli O157:H7 was isolated and screened by culture and latex agglutination respectively. Antibiotics susceptibility of the isolates was performed using multi-disc diffusion method. Data were analysed using descriptive statistics and ANOVA at p<0.05. The residue levels were compared with Codex Alimentarius Maximum Residue Limits (MRLs) and residue prevalence in beef during the wet and dry seasons were also compared. All the respondents administered antibiotics without veterinary prescription, with oxytetracycline being the most commonly used. Most (95.0%) of the producers never observed withdrawal periods and 75% of them did not know the importance of withdrawal i periods and hazards of antibiotic residues. Antibiotic residues prevalence in beef was 48.5%, 44.5% and 44.5% in Ibadan, Lagos and Akure respectively. In chicken, prevalence of 76.0% and 69.5% were obtained in Ibadan markets and farms compared to 70.0% and 61.0% in Lagos markets and farms respectively. Mean oxytetracycline residue concentrations of 1324.7±148.0, 856.6±118.0 and 651.7±101.3µg/kg were obtained in bovine kidney, liver and beef respectively with 37.8, 40.3 and 47.5% of these samples containing residues above MRLs. The levels in chicken liver and muscle were 1042.0±122.8 and 615.0±91.8µg/kg respectively of which 50.7% and 58.8% contained residues above MRLs. The prevalence of antimicrobial residue was significantly higher in chicken than in beef and during wet than dry season in beef. The prevalence of E. coli O157:H7 in beef from Ibadan and Lagos were 28.5% and 11.0%, while those of chicken from Ibadan and Lagos markets were 13.0% and 14.0%, and from Ibadan and Lagos farms were 18.0% and 13.0% respectively. All the isolates were resistant to one or multiple antibiotics, but the highest resistance of 91.1% was to tetracycline. Indiscriminate antibiotics usage predisposes meat consumers to risks of antibiotic residues and resistant Escherichia coli O157:H7 in southwestern Nigeria. Regulatory control of antibiotics usage in livestock production, meat inspection and pharmaco-epidemiological surveillance of food animals is hereby recommended to ensure safe meat supply.